Barriers to accessing health care in Nigeria: implications for child survival - Sunday A. Adedini; Clifford Odimegwu; Olusina Bamiwuye; Opeyemi Fadeyibi; Nicole De Wet (Taylor & Francis Group, 2014)
Background: Existing studies indicate that about one in every six children dies before age five in Nigeria. While evidence suggests that improved access to adequate health care holds great potential for improved child survival, previous studies indicate that there are substantial barriers to accessing health care in Nigeria. There has not been a systematic attempt to examine the effects of barriers to health care on under-five mortality in Nigeria. This study is designed to address this knowledge gap. Data and method: Data came from a nationally representative sample of 18,028 women (aged 15-49) who had a total of 28,647 live births within the 5 years preceding the 2008 Nigeria Demographic and Health Survey. The risk of death in children below age five was estimated using Cox proportional hazard models and results are presented as hazards ratios (HR) with 95% confidence intervals (CI). Results: Results indicate higher under-five mortality risks for children whose mothers had cultural barriers and children whose mothers had resource-related barriers to health care (HR: 1.44, CI: 1.32-1.57, p<0.001), and those whose mothers had physical barriers (HR: 1.13, CI: 1.04-1.24, p<0.001), relative to children whose mothers reported no barriers. Barriers to health care remained an important predictor of child survival even after adjusting for the effects of possible confounders. Conclusion: Findings of this study stressed the need for improved access to adequate health care in Nigeria through the elimination of barriers to access. This would enable the country to achieve a significant reduction in childhood mortality.